Correlation between endoscopic and histological activity in ulcerative colitis using validated indices - Irani, N; Wang, L; Collins, G; Keshav, S; Travis, S (Oxford University Press, 2018)
Background and Aim Endoscopy and histopathology are pivotal for evaluating disease activity in ulcerative colitis (UC); correlation between validated endoscopic and histological indices has not been examined. We aim to correlate the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) with two new validated histological indices in patients with established UC. Methods Retrospective single centre cohort of patients with established UC who underwent flexible sigmoidoscopy or colonoscopy by a single endoscopist. The UCEIS was scored at the worst affected area in the distal colon, which was biopsied; histological disease activity using Nancy (NI) and Robarts’ Histological (RHI) indices was scored by a pathologist blinded to the endoscopy. Spearman correlation between the UCEIS, NI and RHI, and between NI and RHI were performed. Results 125 patients, median age 37 years (range 16-81 years), with UCEIS scores (scale 0-8) 0=21; 1-3=48; 4-6=51; 7-8=5. Correlation coefficients between UCEIS and NI (scale 0-4) were r=0.84 (95% CI 0.76-0.89, p<0.001) and between UCEIS and RHI (scale 0-33) r=0.86 (95% CI 0.80-0.90, p<0.001). The difference in correlation was not significant (p=0.57). There was excellent correlation between the two histological indices (r=0.92, 95% CI 0.87-0.95, p<0.001). Quiescent disease activity defined as the absence of neutrophils (Nancy 0-1, Robarts 0-3) was most closely correlated with UCEIS=0. Conclusions The UCEIS strongly correlates with both NI and RHI. Complete mucosal healing is best defined as a UCEIS=0/8, since this correlates with the absence of microscopic disease activity.